Peran Modal Sosial Bagi Perkembangan Usaha Pedagang Kaki Lima di Era Digitalisasi - Amri, Farhan Hasinul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Social capital is critical in development, be it human and social, economic, and political. It is known that social capital can increase individual awareness of various opportunities that can be developed for the benefit of society, such as the ability to solve complex problems, encourage rapid changes in society, and foster public awareness. In the economic development of social capital, the development and progress of various economic sectors are greatly influenced and even now equipped with sophisticated technology such as cellphones. The value of the concept of social capital is inseparable from social networks, kinship relationships, and social norms. With the existence of social capital, it will produce a positive influence if done optimally, especially for street vendors.